Rotavirus and other viral diarrhoeas (1980)
Recent evidence indicates that viruses are an important cause of acute diarrhoea in infants and young children in both developed and developing countries. This article reviews the available information on the epidemiology, clinical features, and laboratory diagnosis of acute diarrhoea due to two of the more important and recently discovered viruses, namely rotaviruses and the Norwalk and Norwalk-like agents, or to other viral agents. Research priorities are also recommended that will help to elucidate the epidemiology, pathophysiology, and means of preventing viral diarrhoeas. Foremost among these research priorities is the development of a rotavirus vaccine for use in man.